The Health Status of Indigenous and Non-Indigenous Australians - Alison L. Booth; Nick Carroll (Institute for the Study of Labor (IZA), 2005)
We use unique survey data to examine the determinants of self-assessed health of Indigenous and non-Indigenous Australians. We explore the degree to which differences in health are due to differences in socio-economic factors, and examine the sensitivity of our results to the inclusion of ?objective? health measures. Our results reveal that there is a significant gap in the health status of Indigenous and non-Indigenous Australians, with the former characterised by significantly worse health. These findings are robust to alternative estimation methods and measures of health. Although between one third and one half of the health gap can be explained by differences in socio-economic status - such as income, employment status and education - there remains a large unexplained component. These findings have important policy implications. They suggest that, in order to reduce the gap in health status between Indigenous and non-Indigenous Australians, it is important to address disparities in socio-economic factors such as education. The findings also suggest that there are disparities in access to health services and in health behaviour. These issues need to be tackled before Australia can truly claim to have 100% health-care coverage and high levels of health and life expectancy for all of its population.
Keywords: I12; I1; 330; self-assessed health; Indigenous health